2011
DOI: 10.1186/1750-9378-6-24
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of human papillomavirus infection in conjunctival squamous cell carcinoma of Mexican patients

Abstract: BackgroundThe relationship between Human Papillomavirus (HPV) infection and conjunctiva cancer is controversial. HPV detection will provide more information about the role of this infectious agent in the biology of conjunctiva cancer. In the present study, DNA extracted and purified from 36 Conjunctival Squamous Cell Carcinomas (CSCC) was evaluated by PCR for HPV DNA sequences. The results were correlated with the clinical and histopathological variables.ResultsThe results showed that HPV DNA was present in 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
(23 reference statements)
1
13
0
Order By: Relevance
“…Early investigations detected HPV, but several recent studies have not identified the virus in CIN or cSCC lesions, calling its role in the initiation and growth of these tumors into question. [7][8][9] The strong association between OSSN and exposure to sunlight, however, is clear, with a striking increase in their incidence in geographic areas that are close to the equator. 4,10,11 In addition, patients with xeroderma pigmentosum, who are more susceptible to the effects of solar UV light due to mutation or loss of DNA repair factors, are especially prone to develop the disease.…”
mentioning
confidence: 99%
“…Early investigations detected HPV, but several recent studies have not identified the virus in CIN or cSCC lesions, calling its role in the initiation and growth of these tumors into question. [7][8][9] The strong association between OSSN and exposure to sunlight, however, is clear, with a striking increase in their incidence in geographic areas that are close to the equator. 4,10,11 In addition, patients with xeroderma pigmentosum, who are more susceptible to the effects of solar UV light due to mutation or loss of DNA repair factors, are especially prone to develop the disease.…”
mentioning
confidence: 99%
“…This study focused on two geographically separate regions of México: NE and SC (approximately 700 km apart). In the USA, Europe, Sub-Saharan Africa, Latin America and the Caribbean [13][14][15][16], as well as in most Mexican populations investigated so far, HPV 16 has been found to be the most prevalent of the highrisk HPV types in oncogenic malignancies and in asymptomatic women [17]. Our results show this also to be the case in the NE region (with a prevalence of HPV type 16 of 37%/38% in women/men), but not in the SC region (where it was 15%/ 11.5% in women/men).…”
Section: Discussionmentioning
confidence: 99%
“…In one set of studies done in both Africa and the United States, evidence of HPV infection was found in most CSCC tumor samples . In contrast, another set of studies from Africa as well as from other regions of the world such as the United States, Germany, Brazil, and Mexico has found no evidence of HPV in CSCC . In addition, prognostic tumor biomarkers like cyclin D, p16, estimated glomerular filtration rate (EGFR), and p53 have been described in CSCC in the United States, but these are not well studied in CSCC in Africa…”
Section: Introductionmentioning
confidence: 99%